PENGARUH PERILAKU PEDULI LINGKUNGAN DAN HIDUP SEHAT TERHADAP TINGKAT KECERDASAN EKOLOGIS MAHASISWA FKIP UNIVERSITAS KUNINGAN - Irwan Kurniawan; Agie Hanggara (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2019)
Abstract: The problem in this study is the level of ecological intelligence of students towardsenvironmental care behavior and living behavior among students in the FKIP university of brassCompetence is still not good, this can be seen from pre-research data and surveys in the field. Howis the description of Environmental Care Behavior, Healthy Life and Ecological Intelligence Levelof the Teaching Faculty and Kuningan University Education Sciences Students, How does theinfluence of Environmental Care Behavior and Healthy Life on the Ecological Intelligence Levelof Teaching Faculty Students and Kuningan University Education Science, How does theEnvironmental Care Behavior affect Intelligence Levels Ecological Student of the Faculty ofTeacher Training and Education of the University of Kuningan, How the influence of Healthy LifeBehavior on the Level of Ecological Intelligence of the Faculty of Teacher Training and Educationof the University of Kuningan. This study used a survey method conducted on active students inthe 2018 - 2019 period FKIP Kuningan University with a total sample of 309 students, Theinstrument of this study uses a questionnaire or questionnaire that contains the scale ofenvironmental care behavior and healthy living behavior and the level of ecological intelligencethat will be filled by the respondents. Then the instrument test was conducted by validity andreliability testing. After that, data analysis includes descriptive analysis, normality test data andMultiple Regression Analysis. The suggestions that can be given in this study are: Institutions needto form a team that can process and recycle waste, for example by making a garbage bank.Keywords : Environmental Care Behavior, Healty Live Behavior And Ecological IntelligenceLevel